The impact of employee satisfaction as a mediator of compensation and career development on employee performance - Kholilah, Kholilah; Sari, Yukke Sartika (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2021)
The formulation of the problem in this study is 1) Is there any effect of compensation and career development on the satisfaction of PT. Natafari; 2) Is there any effect of compensation and career development on the performance of employees of PT. Natafari; 3) Is there an effect of satisfaction on the performance of the employees of PT. Natafari; 4) Is there any influence of compensation and career development on employee performance through the satisfaction of PT. Natafari. The research objectives are 1) To determine the effect of compensation and career development on the satisfaction of PT. Natafari 2) To determine the effect of compensation and career development on the performance of PT Natafari employees; 3) To determine the effect of satisfaction on the performance of employees of PT. Natafari 4) To determine the effect of compensation and career development on employee performance through the satisfaction of PT. Natafari. This type of research is associative research. The variables used are compensation, career development, satisfaction and employee performance. The sample used is 70 people with the sampling technique using probability sampling. The data used in this study are primary data collected through questionnaires. The data analysis technique used is Path Analysis. The results show that 1) there is a significant effect of compensation on satisfaction and there is no influence on career development on satisfaction 2) there is a significant effect of compensation and career development on employee performance 3) there is a significant effect of satisfaction on employee performance 4) there is a significant effect on compensation and career development about employee performance through satisfaction.